Supervisors Responsibility for Village-Owned Enterprise Bankruptcy - Diky Efra Hutamawida; Widhiadari Widhiadari; Fitro Rizki Ramadhan; Mirza Julma (Borong Newinera Publisher, 2020)
This research is about The unclear regulations related to the juridical construction of village-owned enterprises can certainly causing problems in the case of the Village-Owned Enterprises is unable to pay loan or other debts if they experience business losses. This research uses judicial normative research methodology since the research is aimed to evaluate the regulations found in the formal rules and regulations related to the Village Owned Enterprises (BUM Desa) and the company bankruptcy, namely Regulations Number 6 year 2014 regarding the Village and Regulations Number 37 year 2004 regarding Bankruptcy and the Deferral of Obligation Payment Code and connect with responsibility of village head. The research conclusions show that: firstly, BUM Desa is initially a business entity without having the status as a legal entity, but during its development, it might have the status of a legal entity. Secondly, Supervisors can be responsible for bankruptcy of BUM Desa if it is proven that their fault has caused BUM Desa to go bankrupt